Prospects for NMR imaging in the study of biological morphogenesis. - Lohman, J; Ratcliffe, R (Birkhäuser-Verlag, 1988)
Small objects can be visualised with a spatial resolution that approaches microscopic dimensions using the technique of high resolution nuclear magnetic resonance (NMR) imaging. Some important features of the method are described and the prospects for using the technique to study morphogenesis are discussed. It is concluded that NMR imaging, in conjunction with the related method of localised spectroscopy, is capable of producing novel structural information.